Constructing Identities: Structure and practice in the Early Broze Age - Southwest Norway (AmS-Varia, 2020)
This book explores the construction of regional identities in the Early Bronze Age through the temporal variation in burial practice in Southwest Norway. Earthen barrows from the regions Etne, Karmøy, Jæren, and Lista are used as the archaeological source for this study. How historically constituted structures together with external practice form part of an open-ended process of identity construction is investigated. Previous research has often used a set, rigid definition of identity, and earthen barrows along the coast of Southwest Norway have therefore frequently been portrayed as part of a southern Scandinavian culture. These perceptions are not necessarily wrong, but neglect the complicated processes that give rise to groups. In this study it is argued that patterns found in the material remains, both unintentional and intentional, express regional variation. Through a quantitative methodology based on a selection of focus points and spatial analysis in ArcGIS the multifaceted process behind identity construction is showcased. As a result, the southwest coast of Norway during the Early Bronze Age can be seen as a more complex and dynamic region. Although many similarities between regions are shared, they are also clearly divided and competitive.